Silica polymer nanocomposites functionalized with polyphosphoric acid: A mild catalyst for efficient one-pot synthesis of dihydropyrimidinones under environmentally benign conditions. Issue 7 (3rd July 2017) - Sachdev, Divya
ABSTRACT: An efficient, mild catalyst was employed for the synthesis of dihydropyrimidinones via condensation of aldehyde, ethyl acetoacetate, and urea/thiourea in the presence of silica polymer nanocomposite functionalized with polyphosphoric acid. The present methodology offers an advantage of being mild and highly selective wherein a three-component reaction proceeds proficiently because of the synergistic role of the hydrophobic polymer and the acidic sites functionalized on silica, which allows easy removal of water molecule formed during the reaction.